The Demeter-Persephone myth as writing ritual in the lives of literary women - Norton, Jana Rivers (Cambridge Scholars Publishing, 2016)
"This volume explores the life stories of Elizabeth Bishop, Virginia Woolf, Alice James, and Edith Wharton, whose individuation process mirrored Demeter/Persephone's mythic journey from abduction and rage to purposeful reconciliation. These authors often courted humiliation and consequent exile by voicing what others did not want to acknowledge, yet each took restorative action to discover and preserve emotional and mental wellbeing."--Provided by publisher.